2014
DOI: 10.1159/000363742
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Pseudoaneurysm Manifesting as Delayed Postpartum Hemorrhage after Precipitous Delivery: Three Case Reports

Abstract: Precipitous delivery may lead to serious maternal and neonatal complications. Uterine artery pseudoaneurysm (UAP) is one of the causes of delayed postpartum hemorrhage. Here we describe 3 cases of UAP manifesting as delayed postpartum hemorrhage after precipitous delivery. The duration of the second stage of labor in cases 1, 2, and 3 was 15, 15, and 60 min, respectively. Excessive vaginal bleeding occurred 10, 9, and 31 days after delivery, respectively. Ultrasonogram and pelvic angiography revealed the UAP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…8 The development of a pseudoaneurysm is due to an extraluminal blood collection that has a turbulent communication through an arterial wall defect. 1 The absence of a three-layered arterial wall lining in a pseudoaneurysm differentiates it from a true aneurysm. A UAP may be asymptomatic but usually presents with secondary postpartum hemorrhage (PPH) or delayed vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The development of a pseudoaneurysm is due to an extraluminal blood collection that has a turbulent communication through an arterial wall defect. 1 The absence of a three-layered arterial wall lining in a pseudoaneurysm differentiates it from a true aneurysm. A UAP may be asymptomatic but usually presents with secondary postpartum hemorrhage (PPH) or delayed vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…A pseudoaneurysm is defined as an extraluminal collection of blood with a turbulent flow that communicates with flowing arterial blood through a defect in the arterial wall. 1 Some authors have reported that a uterine artery pseudoaneurysm (UAP) occurs in 2–3/1,000 deliveries. 2 This condition has many causes, such as cesarean section, myomectomy, vaginal delivery, and hysterectomy.…”
mentioning
confidence: 99%
“…For example, when the uterine arteries and its branches ruptured, it mainly manifested with severe vaginal bleeding, [ 31 ] or vaginal bleeding accompanied by pelvic hematoma formation. [ 32 , 33 ] However, when the rupture site was located in the retroperitoneal space, including internal iliac arteries, CIA and the abdominal aorta, the mainly clinical characteristics were retroperitoneal hemorrhage or hematoma, abdomen pain, backache, and lumbago or even chest pain, associated with rapid heart rate, blood pressure changes, and even hemorrhagic shock caused by blood loss. If pseudoaneurysms rupture in the pelvic or abdominal arteries, bleeding will be more ferocious and harmful.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for uterine atony include prolonged labor, an overdistended uterus (e.g. with polyhydramnios, multiple gestation and macrosomia), Couvelaire uterus, high parity, chorioamnionitis, abruptio placentae, placenta previa, placenta accreta/increta/percreta and overuse of tocolytic agents or anesthetic agents [1,2,3,4,8,9,10,11,12]. Early diagnosis and management of risk factors may greatly decrease its incidence.…”
Section: Discussionmentioning
confidence: 99%